2004
DOI: 10.1111/j.1365-2222.2004.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in ADAM33 are associated with allergic rhinitis due to Japanese cedar pollen

Abstract: These results indicate that polymorphisms in the ADAM33 gene are associated with susceptibility to allergic rhinitis due to Japanese cedar pollen, but the functional relationship still needs clarification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
3
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 49 publications
4
22
3
1
Order By: Relevance
“…13,16,27 Of the 37 polymorphisms in ADAM33, studied by Van Eerdewegh et al, 13 six were found to be significantly associated with asthma in a combined the UK/US casecontrol population, and haplotype pair analysis in this population revealed five pairs of SNPs to be significantly associated with asthma at the Po0.001 level and a further 23 pairs to be significant at the Pr0.01 level. Positive associations have also found between some of these polymorphisms and asthma in African Americans and Hispanics, 16 BHR in American Caucasians 16 and Koreans, 33 and atopy and longitudinal FEV 1 decline in Dutch populations, 16,34 allergic rhinitis in a Japanese population, 35 and have also been reported in a German population. 27,36 Interestingly, a recent study in Puerto Rican and Mexican populations failed to show an association between ADAM33, asthma, asthma severity and atopy in these populations (Table 4).…”
mentioning
confidence: 87%
“…13,16,27 Of the 37 polymorphisms in ADAM33, studied by Van Eerdewegh et al, 13 six were found to be significantly associated with asthma in a combined the UK/US casecontrol population, and haplotype pair analysis in this population revealed five pairs of SNPs to be significantly associated with asthma at the Po0.001 level and a further 23 pairs to be significant at the Pr0.01 level. Positive associations have also found between some of these polymorphisms and asthma in African Americans and Hispanics, 16 BHR in American Caucasians 16 and Koreans, 33 and atopy and longitudinal FEV 1 decline in Dutch populations, 16,34 allergic rhinitis in a Japanese population, 35 and have also been reported in a German population. 27,36 Interestingly, a recent study in Puerto Rican and Mexican populations failed to show an association between ADAM33, asthma, asthma severity and atopy in these populations (Table 4).…”
mentioning
confidence: 87%
“…It is clearly of great importance that more is found out about the normal function of ADAM33 and how polymorphic variations may predispose to asthma [81]. Association of the ADAM33 gene with asthma has now been confirmed in Caucasian-, African-and Hispanic-Americans in the Collaborative Study on the Genetics of Asthma [82] and separate populations in the Netherlands [82], Germany [83], Korea [84] and Japan [85] and in a large meta-analysis involving Icelandic, Mexican and Puerto Rican, as well as European, populations [86]. In this latter study, there were several populations which, when analysed alone, failed to reveal significance but together resulted in strong association, thereby emphasising the importance of combining data.…”
Section: Disease Linkage Analysis and Positional Cloningmentioning
confidence: 99%
“…Several studies have reported analysis of the association of SNPs with allergic rhinitis. Cheng et al (2004) reported that polymorphisms in disintegrin and the metalloprotease domain 33 (ADAM33) gene are associated with susceptibility to allergic rhinitis in the Japanese population. Polymorphisms of IL-13 were associated with allergic rhinitis susceptibility and might be responsible for the high IgE level in allergic rhinitis patients (Wang et al 2003).…”
Section: Applicationmentioning
confidence: 99%